If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -64 = 64 Reorder the terms: -64 + X = 64 Solving -64 + X = 64 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '64' to each side of the equation. -64 + 64 + X = 64 + 64 Combine like terms: -64 + 64 = 0 0 + X = 64 + 64 X = 64 + 64 Combine like terms: 64 + 64 = 128 X = 128 Simplifying X = 128
| hj=3(x+2) | | 7-2x=12-5x | | 16-x=2 | | 4m-12+24=92 | | 6.162-0.9n=9-5.3(1.8n-3.54) | | 20p^2-100pq+125q^2=0 | | 3(x-1)=4(5+2x) | | xxx=64 | | 0.2(x+3)-4(2x+3)=0.9 | | 1.5(x-1)=x+3 | | 2x^2-23x+57=0 | | 64r^2-9t^2=0 | | -36=6 | | -8-x/7=-8 | | -7r-21=-63 | | 4x=36+4x | | 100=45+14.99x | | 17+3x=28x-28 | | 8.2+(-1.5)=k | | -39=-3(-3m+7) | | 8x-8=4x+3 | | 96=24a | | 8.2+(-1.5)= | | 3b-5b+6b= | | 12d+2-3d= | | 1706=110x+56 | | z^30+275=1225 | | -3a-(-12)=19 | | 62x+9=5x+8 | | k=8.2+(-1.5) | | 4x^2-4x=11 | | 211,200=660w |